STOCK DIVERSIFICATION (PORTFOLIO) STRATEGY TO INCREASE INVESTMENT RETURNS AND REDUCE RISK - Deby Shintawulan Fransiska; Novita Rahmawati; Feby Galih Saputra; Maria Yovita R Pandin (Finance : International Journal of Management Finance, 2023)
The purpose of this article is to explain diversification and portfolio risk and the impact of diversification on portfolio risk and determine the number of stocks that make up the optimal portfolio. The sampling technique is purposive sampling and the sample is taken from 5 stocks of the IDX Energy Sector industry. The analysis tool uses a correlation matrix, expected return and risk for individual stocks and portfolios (5 stocks) and the Unknown Population Standard Deviation (σ) Hypothesis Test. The results of this study are: 1)                The correlaion matrix table shows that stocks have a positive correlation, meaning that the stock price movement is in the same direction, that is, when the price of one stock rises, the price of the other stock will rise. Of the five correlations that occur, the correlation between AKRA and ADRO stocks has the largest positive correlation coefficient. And the correlation between MEDC and ADRO stocks has the smallest correlation coefficient. 2)                In general, the expected return and risk performance of the portfolio is better than the performance of individual stocks. So by applying stock diversification, the return performance can be optimized, and risk can also be minimized. 3)                From the results of the Hypothesis Test Population Standard Deviation (σ) is Unknown. The t statistic value of - 5.334 is in the area > - 0, 1771. Then the decision is that the null hypothesis (Ho) is rejected. This means H1 is accepted, i.e. the risk of stock diversification is smaller than the risk of individual stocks.